Usability evaluation of an augmented reality application for ship design learning: Evidence from Nielsen’s Attributes of Usability - Muhammad Irsyad Khairi; Amirul Mu'minin (Jurnal Pendidikan Vokasi, 2025)
The rapid shift toward digital and immersive learning environments has encouraged the use of Augmented Reality (AR) as an instructional medium capable of visualizing complex objects. However, studies examining AR in maritime vocational contexts — particularly ship design — remain limited, and usability-driven development approaches are rarely documented. This study aims to design and evaluate the usability of the EV. Hadapera AR application for ship design learning, focusing on students’ user experience when interacting with immersive 3D learning content. The research adopted a Research and Development approach in combination with the Double Diamond design framework, while usability was assessed using Nielsen’s Attributes of Usability (NAU). A total of 30 students from the Ship Construction Engineering Technology program participated and completed a usability questionnaire following hands-on application use. Data were analyzed using validity and reliability testing, followed by descriptive calculations of usability scores. Results indicate excellent usability performance across learnability (87.6%), satisfaction (85.2%), efficiency (83%), and memorability (82.6%), with the error dimension rated good (79%), producing an overall usability level of 83.48%. These findings demonstrate that the application is intuitive, engaging, and supportive of interactive exploration of ship structures through mobile-based AR. This study contributes empirical evidence on usability-oriented AR design in maritime vocational education and highlights the relevance of NAU as an evaluation framework for immersive learning tools. Future research should expand to larger samples, include multi-device testing, and integrate learning-outcome measurements to complement usability results.